Effect of Exogenous Melatonin on the Quality of Soybean and Natto Products under Drought Stress. (20th April 2021) - Cao, Liang; Kou, Fang; Zhang, Mingcong; Jin, Xijun; Ren, Chunyuan; Yu, Gaobo; Zhang, Yuxian; Wang, Mengxue
Abstract : Melatonin can directly or indirectly eliminate reactive oxygen species, regulate hormone levels, and improve drought-stressed soybean crop resistance, yield, and quality. The nutrient contents of soybeans grown under normal conditions (WW), drought stress (D), and drought stress with exogenous melatonin (D + M) (p < 0.05 ) were compared. The differences in the quality of natto from the three groups of soybeans were also analyzed. The results showed that compared with soybeans under normal conditions, those grown under drought stress had reduced yield and carbohydrate, protein, essential amino acid, soybean isoflavone, and other nutrient contents. Besides, natto presented low nattokinase levels (674 U/mL), natto drawing ability was weak, the surface was dull, the taste was poor, and the sensory score was 12 points. Exogenous melatonin increased the carbohydrate content (starch, sucrose, glucose, and fructose) and improved the yield and quality of soybeans under drought. The natto produced by soybeans under drought stress with exogenous melatonin had high nattokinase content (756 U/mL) and long wire drawing. The surface of the product was rich in mucus and had a natto aroma. Its comprehensive sensory score was 20 points. Natto from soybeans under drought stress that were treated with exogenous melatonin showed significantly higher yield, nutrient content, and quality, than those under drought stress without treatment. This study provides theoretical data that can facilitate the development of new methods to improve the quality of soybeans grown under drought conditions.